Awareness And Use of e-Resources among Research Scholars of Social Science Faculties in Selected Universities of Bihar: A Survey (LIS TODAY, 2025)
Purpose: The increasing use of electronic resources (e-resources) has transformed  the landscape of academic research and knowledge dissemination and it has  become necessary for library professionals to study its utility. The aim of this  study is to examine the awareness and usage of e-resources among research  scholars in the Faculty of Social Sciences in universities of the state of Bihar.  Methodology: This study employed a mixed-methods approach, consisting of a  survey and semi-structured interviews, to collect data from a sample of 110 research  scholars from various social science disciplines across five government universities in  the state of Bihar. Findings: The findings indicate that the level of awareness about  e-resources among research scholars is very high, and most respondents regularly use  these resources for their research work. However, the study also highlights the need for  better access, training and institutional support to further improve the effective use of  e-resources. The findings reveal a significant correlation between awareness levels and  the effective use of e-resources, highlighting the need for improved training and access. Originality: This is the first research of its kind on the use and awareness of e-resources  by research scholars of the Faculty of Social Sciences of universities in Bihar. These  results provide valuable insights for academic institutions in Bihar to develop targeted  strategies and policies that promote the integration of e-resources in the research and  academic activities of their stakeholders.
Keywords: E-Resources; Electronic Resources; Research Scholars; Social science; Universities of Bihar